2005
DOI: 10.2337/diacare.28.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Mortality and Diabetes Complications in Patients With Type 1 and Type 2 Diabetes

Abstract: OBJECTIVE—Diabetes is a leading cause of morbidity and mortality. The purpose of this study is to assess the associations between diabetes complications and mortality in the Early Treatment Diabetic Retinopathy Study (ETDRS). RESEARCH DESIGN AND METHODS—We examined demographic, clinical, and laboratory characteristics of the 3,711 subjects enrolled in the ETDRS, a randomized controlled clinical trial designed to evaluate the role of laser photocoagulation and aspirin therapy for diabetic retinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
3
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 66 publications
9
124
3
4
Order By: Relevance
“…Furthermore, vision loss due to retinopathy is a serious complication of diabetes and is associated with significant morbidity including increased falls, hip fractures and a fourfold increase in mortality [2,29]. A large American study conducted in the largest county in Los Angeles evaluated the use of teleretinal diabetic retinopathy screening (with optometrists conducting the analysis) and found improved efficiency, quality and access to care [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vision loss due to retinopathy is a serious complication of diabetes and is associated with significant morbidity including increased falls, hip fractures and a fourfold increase in mortality [2,29]. A large American study conducted in the largest county in Los Angeles evaluated the use of teleretinal diabetic retinopathy screening (with optometrists conducting the analysis) and found improved efficiency, quality and access to care [30].…”
Section: Discussionmentioning
confidence: 99%
“…All-cause mortality rate per 1,000 personyears was 15.3 in type 1 diabetic men, 10.3 in type 1 diabetic women, 15.6 in type 2 diabetic men, and 16.1 in type 2 diabetic women in the age-group of 50 -59 years (13). In contrast, the World Health Organization Multinational Study of Vascular Disease in Diabetes Study demonstrated that type 2 diabetic women had lower relative CVD mortality compared with that in type 1 diabetic subjects and type 2 diabetic men (14).…”
Section: -Total and Cvd Mortality During 18 Years Of Follow-up In Typmentioning
confidence: 99%
“…Since both entities have previously been shown to be independent predictors of mortality [4,5], the aim of the present study was to measure p75NTR immunoreactivity semi-quantitatively in patients with type 2 diabetes and to investigate correlations with different aspects of diabetic neuropathy.…”
mentioning
confidence: 99%